ANALISIS STANDAR JUMLAH PERSONEL PENANGANAN PENGANGKUTAN BARANG BERBAHAYA DI BANDAR UDARA ADISUTJIPTO - Gunawan, Gunawan; Medianto, Rully (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
Good and efficient Air cargo handling, especially for dangerous goods transportation need to be supported by licensed dangerous goods handling personnel and supported by the transport handling facilities as well as standard procedure. Comprehensive standards and procedures are required to reduce the risk of accidents caused by an error in the handling of the dangerous goods transportation. Main problems in this study: first, to analyse the process of air cargo transportation handling at the Adisutjipto Airport; second, to analyse the standard of the dangerous goods handling personel. The cargo handling process consists of Outgoing (Acceptance, weighing, Documentation, Marking & labeling, X-ray, Storage, Build-up, and Loading) and Incoming (Check Incoming Massage, Unloading, Breakdown, check lists, Physical Examination, Storage, Notice of Arrival, Delivered). The mathematical model of Dangerous Goods Handling Personnel Number Standard: DG Personel Cargo Agent Type A = c.% DG. (2,89 x 10^-2) DG Personnel Warehousing Type B = c.% DG (4,53 x 106-3), DG Personnel Airline Type B = c.%DG. (4,89 X 10^-4).